PENGETAHUAN PETUGAS KESEHATAN DAN LINTAS SEKTOR TENTANG LEPTOSPIROSIS DI KABUPATEN PATI - Aryani Pujiyanti; Dimas Bagus Wicaksono Putro; Arief Mulyono (Vektora : Jurnal Vektor dan Reservoir Penyakit, 2019)
Leptospirosis control in Pati Regency cannot rely on the general health sector alone, however, it is needed collaboration between the cross-program in leptospirosis control and the relevant sectors. This study aimed to describe the level of leptospirosis knowledge of the health and the cross-sectors officers in Pati Regency, Central Java Province through the assessment activity. A cross-sectional method was used in the present study. A total of 32 people consisting of the the health and the cross-sectors officers was used as research subjects. They attended the dissemination of leptospirosis held in April 2018 . The instrument used was a questionnaire and the data collection was performed using the questionnaire technique. The data were analyzed descriptively using fisher exact analysis. The results showed that most respondents had a good level of leptospirosis knowledge. There was no significant positive correlation between resondents' knowledge with age, education level, gender, and type of institution. Respondents understood that environmental factors and the presence of rats played a major role in leptospirosis transmission in Pati District. However, most respondents were lack of knowledge on the role of non-rats as leptospirosis reservoirs. The knowledge of leptospirosis prevention was focused on on self-protecting against bacterial contact from the environment rather than efforts of rodents control and the use of gloves when treating animals. The District Health Office is recommended to provide the health education on leptospirosis issues for both the cross programs and across sectors officer, particularly how to control rats and the role of non-rats as leptospirosis reservoirs.